2005
DOI: 10.1097/01.ten.0000185155.58515.58
|View full text |Cite
|
Sign up to set email alerts
|

Unexpected Detection of an Intrathymic Parathyroid Adenoma by Tc-99m-MIBI Scintigraphy

Abstract: Although most parathyroid adenomas are located in the neck, approximately 25% of them are found deep in the mediastinum. These ectopic adenomas are one of the major causes for failure of bilateral neck exploration because it is almost impossible to reach deep mediastinal tissues from a standard neck incision unless sternotomy is performed. So, although preoperative localization methods are not routinely recommended for the surgical planning of primary hyperparathyroidism, whenever ectopic parathyroid tissues i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 10 publications
0
3
0
1
Order By: Relevance
“…The EPAs have a variable incidence according to many studies ( 3 , 14 , 15 ). Phitayakorn et al ( 16 ), in a series of 231 patients who underwent surgery for hyperparathyroidism, reported that 16% were ectopic lesions, among which 3% were intra-thymic ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The EPAs have a variable incidence according to many studies ( 3 , 14 , 15 ). Phitayakorn et al ( 16 ), in a series of 231 patients who underwent surgery for hyperparathyroidism, reported that 16% were ectopic lesions, among which 3% were intra-thymic ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…The ectopic parathyroid adenomas have a variable incidence according to many reported studies [4,5]. Phitayakorn and Mc Henry, in a series of 231 patients operated for hyperparathyroidism, had reported 16% of ectopic lesions among which 3% were intra-thymic [6].…”
Section: Discussionmentioning
confidence: 99%
“…The incidence of ectopic intrathymic parathyroid adenomas varies according to authors. 3,4 In the Phitayakorn and Mc Henry 5 series of 231 patients operated for hyperparathyroidism, 16% had ectopic lesions; of which, 3% were intrathymic. In fact, the lower parathyroids and the thymus have a common embryological origin from the third branchial pouch before their respective cervical and mediastinal migration.…”
Section: Discussionmentioning
confidence: 99%